Pengaruh Biofilter Rumput Laut Gracilaria sp. terhadap Dominansi Plankton pada Media Air yang Terpapar Logam Berat Cr [Effect Of Biofilter Of Seaweed Gracilaria sp. To Plankton Domination On Water Medium That Exposed To Heavy Metal Chromium (Cr) ] - Sudarno Sudarno; Tantika Wulan Sari; Amin Alamsjah (Jurnal Ilmiah Perikanan dan Kelautan, 2013)
Abstract Pollution is entered or the inclusion of living things, matter, energy, and or other components into the water. The study shows that the qualitative waters affected Sidoarjo mud Lapindo has the value of pollution index (13.3433), Sidoarjo heavily polluted coastal waters, and to sustain the cultivation of water treatments required physical, chemical and biological before the water is used for maintenance (Sudinno, 2009). Associated with the food chain, plankton have properties capable of accumulating pollutants in the environment. Pollutants in the environment are accumulated by plankton forming toxin becomes toxic compounds. There is a selection of flora and fauna to be used either as a biofilter, bioakumulator well as pollution biomonitoring agent occurs in the waters of the sea grass Gracillia sp. Giving Gracilaria sp. with different doses expected to affect the dominance of plankton in the water media exposure of heavy metals Cr. Once the research is done, it turns out the levels of heavy metals chromium (Cr) has been dropped from the initial 0.18 mg / l to 0.09 mg / l in the sediment. There Tetraselmis chuii plankton dominance in aqueous media, dominance of plankton in the water medium to portray the diversity of aquatic environments with low plankton, and this is not good for plankton and other organisms that utilize the natural feed.